Depot-specific differences in inflammatory mediators and a role for NK cells and IFN-gamma in inflammation in human adipose tissue - O'Rourke, R.W; Metcalf M.D; White, A.E; Madala, A; Winters, B.R; Maizlin, I.I; Jobe, B.A; Roberts, C.T. Jr; Slifka, M.K; Marks, D.L (International Journal of Obesity, 2009)
Background: Adipose tissue is a primary in vivo site of inflammation in obesity. Excess visceral adipose tissue (VAT), when compared to subcutaneous adipose tissue (SAT), imparts an increased risk of obesity-related comorbidities and mortality, and exhibits differences in inflammation. Defining depot-specific differences in inflammatory function may reveal underlying mechanisms of adipose-tissue-based inflammation. Methods: Stromovascular cell fractions (SVFs) from VAT and SAT from obese humans undergoing bariatric surgery were studied in an in vitro culture system with transcriptional profiling, flow cytometric phenotyping, enzyme-linked immunosorbent assay and intracellular cytokine staining. Results: Transcriptional profiling of SVF revealed differences in inflammatory transcript levels in VAT relative to SAT, including elevated interferon- (IFN-) transcript levels. VAT demonstrated a broad leukocytosis relative to SAT that included macrophages, T cells and natural killer (NK) cells. IFN- induced a proinflammatory cytokine expression pattern in SVF and adipose tissue macrophages (ATM). NK cells, which constitutively expressed IFN-, were present at higher frequency in VAT relative to SAT. Both T and NK cells from SVF expressed IFN- on activation, which was associated with tumor necrosis factor- expression in macrophages. Conclusion: These data suggest involvement of NK cells and IFN- in regulating ATM phenotype and function in human obesity and a potential mechanism for the adverse physiologic effects of VAT.